SPORTS VOLUNTEERING: ABSTRACT AND ANALYTICAL REVIEW - Seiranov S.G.; Myagkova S.N.; Aleksandrov B.Yu.; Barienikova E.E. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the main directions of the formation and development of the theoretical and methodological basis of research on the issues of sports volunteering. Methods and structure of the study. An array of scientific papers on the subject of sports volunteering has been systematized. Results and conclusions. The topic of the sports volunteer movement in Russia is of academic interest from the scientific community: teachers, sociologists, economists, historians and managers. In their research, scientists and practitioners agree that in order to effectively organize their work, sports volunteers must have systemic knowledge about sports and the specifics of sports competitions. The scope of the work of a sports volunteer is quite wide and varied: from performing elementary control or warning functions to solving issues that require serious preparation. Thus, a modern mass, international sports event cannot take place without the involvement of sports volunteers, the organization and training of which remains a very urgent task for the industry to this day.